Primary Curriculum Development History of Elementary Curriculum Development in Indonesia - Diniarty puluhulawa; Sri Yuliyani Monoarfa; Nurul Waliya Uno; Aulia Mahmud; Sri Yanti Ali; Nur Fazria Tangahu; Siti Mutia Albakir; Dennis Angelina; Nursia Dulman (International Journal of Advanced Technology and Social Sciences, 2023)
Education continues to develop over time, aiming to improve the quality of education itself. This article was created so that readers better understand the development of the curriculum in Indonesia from time to time which underwent changes starting from the 1947 1952 1964 1966 1998 1975 1984 1994 1999 2004-2006 2003 curriculum until independence of learning. In this article we use several methods to search for material that will be included in the article, namely data collection methods which include collecting data from several books, articles and journals as well as collecting data from the internet